2010
DOI: 10.1152/ajpheart.00822.2009
|View full text |Cite
|
Sign up to set email alerts
|

Stretch-induced hypertrophy of isolated adult rabbit cardiomyocytes

Abstract: Blaauw E, van Nieuwenhoven FA, Willemsen P, Delhaas T, Prinzen FW, Snoeckx LH, van Bilsen M, van der Vusse GJ. Stretch-induced hypertrophy of isolated adult rabbit cardiomyocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 54 publications
0
37
0
Order By: Relevance
“…By contrast, SRF and NFATc4 (both known target genes of miR‐133a) did not show any relation with miR‐133a in this study and are most likely not involved in the hypertrophic response in our model of local hypertrophy. In vitro studies showed that increased CTGF expression in isolated, stretched cardiomyocytes coincided with development of a hypertrophic response 1, 3. Moreover, in a rabbit model of eccentric hypertrophy, where strains and workload are expected to be high throughout the LV wall, CTGF was also found to be overexpressed 3.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…By contrast, SRF and NFATc4 (both known target genes of miR‐133a) did not show any relation with miR‐133a in this study and are most likely not involved in the hypertrophic response in our model of local hypertrophy. In vitro studies showed that increased CTGF expression in isolated, stretched cardiomyocytes coincided with development of a hypertrophic response 1, 3. Moreover, in a rabbit model of eccentric hypertrophy, where strains and workload are expected to be high throughout the LV wall, CTGF was also found to be overexpressed 3.…”
Section: Discussionmentioning
confidence: 97%
“…However, in vivo , it is difficult to separate the contribution of (local) mechanical load and (systemic) neurohumoral activation, because global cardiac overload, as in hypertension and valvular disease, also leads to neurohumoral stimulation/activation. On the other hand, it has been shown that stretching isolated cardiomyocytes can affect gene expression, increase protein synthesis, and induce hypertrophy 1. Similarly, stretching isolated cardiac fibroblasts increases expression of extracellular matrix (ECM) genes and proteins 2, 3…”
Section: Introductionmentioning
confidence: 99%
“…In response to cyclic mechanical strain, cardiac myocytes in vitro become hypertrophic, as signified by increases in cell size and overall protein expression [19,32,46,158] and the activation of fetal gene programs [63]. Therefore, cyclic stretch is an extrinsic cue that induces intrinsic changes in gene expression, presumably to equip the myocyte to better cope with the mechanical load.…”
Section: Gene Expressionmentioning
confidence: 99%
“…For example, cardiac hypertrophy and heart failure are reproduced in the rat by ligating coronary arteries or by using the spontaneously hypertensive rat strain (15). In vitro, heart disease has been modeled by exposing primary cardiac myocytes to chemical (16) or exogenous mechanical stimuli (17)(18)(19)(20)(21), which increases cell size, activates pathological gene expression, and remodels ion channel currents. However, cell culture systems often fail to predict the efficacy or toxicity of therapeutic candidates, potentially because they do not replicate the complex structurefunction relationships of native cardiac tissue (22).…”
mentioning
confidence: 99%